Tingkat Kardiorespirasi Atlet Bola Voli Putri Profesional berdasarkan Indikator VO2max - Nicky Valliana Rafael; Rendra Kusuma; Feri Weldani (SPRINTER: Jurnal Ilmu Olahraga, 2026)
Although VO2max is important in sports, there is still a lack of research conducted on professional volleyball athletes. Some studies remain limited and exhibit wide variations. The purpose of this study was to determine the VO2max levels of professional female volleyball players and compare them with those of female volleyball athletes in Asia and worldwide. This study used a comparative, descriptive, quantitative approach. The design used was a cross-sectional design, which took measurements at a single point in time. The sample for this study was purposively selected from 14 people. The instrument used to measure VO2max values ​​was the Balke 15-Minute Run Test. The average VO2max of participants was 39.0±4.2 ml/Kg/sec with a range of 33.5 to 43.7 ml/Kg/sec. Therefore, the cardiorespiratory fitness level of female professional volleyball players in this study, as indicated by VO2max, is below the standards for female volleyball athletes in Asia and Europe but still superior to that of the Indonesian university student population.